2014
DOI: 10.1093/nar/gkt1371
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor NIR interacts with the p53-inhibiting ubiquitin ligase MDM2

Abstract: NIR (novel INHAT repressor) can bind to p53 at promoters and inhibit p53-mediated gene transactivation by blocking histone acetylation carried out by p300/CBP. Like NIR, the E3 ubiquitin ligase MDM2 can also bind and inhibit p53 at promoters. Here, we present data indicating that NIR, which shuttles between the nucleolus and nucleoplasm, not only binds to p53 but also directly to MDM2, in part via the central acidic and zinc finger domain of MDM2 that is also contacted by several other nucleolus-based MDM2/p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Tera-1 cells were grown at 37°C and in a 5% CO 2 atmosphere in McCoy's 5a medium, while The proteins were separated by SDS-PAGE, immobilized on PVDF membrane (Immobilon P, Millipore) and detected by the indicated antibodies 65 .…”
Section: Cell Cultures and Transfectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tera-1 cells were grown at 37°C and in a 5% CO 2 atmosphere in McCoy's 5a medium, while The proteins were separated by SDS-PAGE, immobilized on PVDF membrane (Immobilon P, Millipore) and detected by the indicated antibodies 65 .…”
Section: Cell Cultures and Transfectionsmentioning
confidence: 99%
“…GST pull-down analyses were performed by immobilizing equal amounts of GST, GST-MDM2, GST-MDM2 deletion mutants, or GST-Np9, respectively, on Gluthation-Sepharose beads (GE-Healthcare), following the protocol published by us recently 65 …”
Section: Gst Pull-down Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mutant p53 is able to convert 1,25-D 3 from a pro-to an antiapoptotic agent (16 Considering the high physiological relevance of wild-type p53 as major barrier to cancer progression, our new finding will encourage future studies to elucidate the significance of the association of both proteins. Remarkably, our study identified new nuclear VDRbinding partners that control p53-mediated biological effects, including the novel inhibitor of histone acetyl transferases (INHAT) repressor NIR, which modulates the transcriptional activity of p53 and of its relative p63 (6,17,18) as well as nuclease-sensitive element-binding protein 1 (19), ELAV-like protein 1 (20)(21)(22) and nucleophosmin (23). Our MS data that indicate VDR binding to nuclear located mediator of RNA polymerase II (Table I) are in line with the results of Rachez and coworkers.…”
Section: Resultsmentioning
confidence: 99%
“…), as well as for transactivation via binding of NCoAs. It has been reported that VDR-NCoAs interfaces correspond to helices H3 and H12 (the latter representing the activation function-2 domain), and an area immediately Nterminal of the zinc fingers (residues [18][19][20][21][22]. Binding of human VDR to basal transcription factors such as transcription factor II B (TFIIB) (near the N-terminus of VDR), as well as with transcriptional corepressors such as the hairless (Hr) gene product, which associates with the VDR hinge and H3, have also been shown before (26).…”
Section: Resultsmentioning
confidence: 99%